Effects of rainfall and groundwater level on soil subsidence, water content, and yield of oil palm. Issue 1 (May 2021) - Adhi, Y A; Mubarak, H; Roland, R; Utama, P P; Tambusai, N; Ismail, I; Anwar, S; Tarigan, S D; Sahari, B
Abstract: Peatlands have long been cultivated for various agricultural crops in Indonesia. However, nowadays land fires are often associated with drained peatlands. We present a four-year study looking at the effects of groundwater level (GWL) on peat reduction, moisture content, and yield. Observations were made on oil palm plantations in tropical peatlands of Riau Province. GWL was observed in 417 plots of 139 blocks and recorded once a week. Peat moisture was monitored automatically and recorded every hour. Subsidence poles were made in 36 blocks and recorded once a month. The results showed that peat subsidence, water content, and yield were affected by GWL fluctuations. There is a relationship between GWL and changes in peat subsidence (R2 = 0.26). A strong relationship was seen between the GWL and the water content of the peat soil at the 10 cm layer (R2 = 0.65). A strong relationship was also found between GWL and oil palm yield 20 months later (R2 = 0.65). In conclusion, by maintaining GWL at a depth of 40-60 cm, peat moisture at the surface can be maintained, peat subsidence can be minimized and oil palm production remains high at an average of 22 tonnes year-1, thereby also reducing susceptibility to fire.